2008
DOI: 10.1111/j.1742-4658.2008.06583.x
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization and in vivo insulin‐induced translocation of the insulin‐signaling inhibitor Grb14 in rat liver

Abstract: Grb14 is a member of the Grb7 ⁄ Grb10 ⁄ Grb14 family of adaptor proteins, which lack intrinsic enzymatic activity and share a common multidomain structure.These adaptors bind to several receptor tyrosine kinases and signaling proteins, and are involved in the regulation of various processes, including cell growth and The molecular adaptor Grb14 binds in vitro to the activated insulin receptor (IR) and inhibits IR signaling. In this study, we have used rat liver subcellular fractionation to analyze in vivo insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
2
13
0
3
Order By: Relevance
“…Moreover, an increase in IR transit through endosomes was observed with [Arg A0 ]-HI, which may originate from: (1) the conversion of [Arg A0 ]-HI into HI, which may delay the dissociation of insulin peptides from the endosomal IR and its subsequent recycling; (2) a reduced dissociation of [Arg A0 ]-HI-receptor complex at the fluctuating endosomal pH compared with HI-receptor complex; and (3) a serum half-life of [Arg A0 ]-HI longer than that of HI. Interestingly, as previously reported for the protease-resistant H2-analogue [15,24], [Arg A0 ]-HI induced an increase in the kinetics of MAP kinase activation and a more sustained association of GRB14 with the hepatic endosomes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, an increase in IR transit through endosomes was observed with [Arg A0 ]-HI, which may originate from: (1) the conversion of [Arg A0 ]-HI into HI, which may delay the dissociation of insulin peptides from the endosomal IR and its subsequent recycling; (2) a reduced dissociation of [Arg A0 ]-HI-receptor complex at the fluctuating endosomal pH compared with HI-receptor complex; and (3) a serum half-life of [Arg A0 ]-HI longer than that of HI. Interestingly, as previously reported for the protease-resistant H2-analogue [15,24], [Arg A0 ]-HI induced an increase in the kinetics of MAP kinase activation and a more sustained association of GRB14 with the hepatic endosomes.…”
Section: Discussionsupporting
confidence: 79%
“…Administration of HI [24] or arginyl-insulins did not cause detectable changes in the levels of IRS-1 or SHC isoforms at the endosomal locus. In contrast, the three ligands led to a rapid increase in the content of the molecular adaptor GRB14 within EN fractions [15]. Endosomal association of GRB14 was more sustained after the administration of [Arg A0 ]-HI, which paralleled its effect on phosphorylated IR-β content.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Une injection d'insuline induit en 30 secondes la fixation de Grb14 sur le récepteur dans le foie de rats, et l'interaction se poursuit tant que le récepteur est activé et phosphorylé. En effet, une analyse par fractionnement cellulaire de ces foies a démontré que Grb14 reste associée au récepteur de l'insuline depuis son activation à la membrane plasmique jusqu'aux endosomes où le récepteur est finalement séparé de l'insuline et retourne à sa conformation inactive [40]. Il est bien établi que le récepteur de l'insuline est rapidement internalisé dans les endosomes après l'activation par la liaison de son ligand, et que les récepteurs présents dans les endosomes sont actifs en termes de transduction du signal [41,42].…”
Section: Mécanismes Moléculaires De L'action De Grb10 Et Grb14 Sur Launclassified
“…The Grb14 expression level is thus inversely correlated with insulin sensitivity in human and animal models of insulin resistance. We previously reported that Grb14 is recruited to the activated insulin receptor and inhibits its catalytic activity and downstream insulin signaling (5,11,12). Furthermore, Grb14 expression is stimulated by insulin, suggesting that it might be involved in a negative feedback loop of insulin signaling and action (9).…”
mentioning
confidence: 99%